The Impact of Management Information Systems on The Corporate Performance within The Period from 2015 to 2017 : A Case Study On Al Naghi Motors Company, Jeddah, kingdom of Saudi Arabia - Abdel Rahman, Balsam Saeed; Trabelsi, Mariam Al-Arabi; Bilal, Eve Abdullah; Hamad, Hafez Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2019)
The research aimed to identify the impact of management information systems on the performance of Al Naghi Motors Company from the perspective of the staff. In addition to that, the research also aims to study the constraints and problems and propose solutions that would improve the performance of Al Naghi Motors Company. The researcher depends on the descriptive and analytical method(s) to study the case. It is noteworthy that the data obtained from the field study were statistically processed by using statistical program SPSS. The questionnaire method was also used as a tool for the study. The researcher has concluded to many results out of which: there is a significant impact for management information systems on the company’s performance which is represented in focusing on the importance of the information security strategy; and coping with the most updated software considering the quality standards at the time of importing the appliances. Further, there is an apparent strategy for upgrading its human resources which is represented in the availability of high specialized human resources. The study also concluded to recommend that a serious reflection is highly required to establish an internal network (Internet) provided that to consider establishing a comprehensive database for all the car sales activities in all the branches of Al-Naghi Motors Company throughout the kingdom; and planning for (developing) semi continuous training programs. in the information systems should be taken into account. In addition to that activation of electronic applications is highly required ( is of a high necessity), to help all the personnel in the company to send their problems and queries through such application in order to enable the concerned department to immediately deal with.